Accepting your Body after Cancer (ABC), a group-based online intervention for women treated for breast cancer: study protocol for a feasibility randomised controlled trial - Sarah Byford; Abigail Jones; Shelley Potter; Paul White; Diana Harcourt; Helena Lewis-Smith; Patricia Fairbrother (BMJ Open)
Introduction Breast cancer is the most common cancer among women worldwide. While increasing numbers of women are living beyond breast cancer, treatment-related body image concerns are common and associated with adverse consequences. Nonetheless, rigorously evaluated and effective body image interventions are lacking among this group. Accepting your Body after Cancer (ABC) has indicated promise in relation to inperson delivery. However, online delivery may increase accessibility and facilitate sustainability of the intervention. Therefore, we aim to establish the feasibility of conducting a fully powered randomised controlled trial to evaluate online delivery of ABC.Methods and analysis 120 women who have received treatment for breast cancer and are experiencing body image concerns will be randomised equally to either the ABC or standard care control group. All participants in both conditions will receive a body image booklet for people who have had cancer. ABC participants will also take part in a weekly seven-session, group-based cognitive behavioural therapy intervention, delivered online by a psychologist and cancer support specialist. Outcome measures will be completed at baseline and 9 weeks, 20 weeks and 32 weeks post baseline. Quantitative data on recruitment, retention, ABC attendance and questionnaire completion rates will be analysed using descriptive statistics. Qualitative data will also be collected to better understand the feasibility and acceptability of the research process and intervention, with data analysed using ‘codebook’ thematic analysis.Ethics and dissemination The study has received ethical approval from the Newcastle North Tyneside Research Ethics Committee (ref: 24/NE/0092). The findings will be disseminated to academic and health professionals via a peer-reviewed publication and presentations at relevant conferences. Results will also be disseminated to participants, national cancer organisations and the general public via accessible reports, online presentations and different communication channels.Trial registration number ClinicalTrials.gov NCT06412341; ISRCTN ISRCTN88199566; IRAS 327507; REC reference 24/NE/0092; funder reference NIHR205415.